Chemotherapy-Induced Hair Loss: The Use of Biomarkers for Predicting Alopecic Severity and Treatment Efficacy. Issue 14 (April 2019) - Haslam, Iain S; Smart, Eleanor
Damage to hair follicles following exposure to toxic chemotherapeutics can cause substantial hair loss, commonly known as chemotherapy-induced alopecia (CIA). Preventive therapies remain limited; however, recent advances in the use of scalp cooling technologies have proved successful in preventing or reducing hair loss in some patients. Further improvements in scalp cooling efficacy and/or development of novel treatments to prevent chemotherapy-induced hair loss are required. To achieve this, post-chemotherapy assessment of hair follicle damage markers, with and without scalp cooling, would provide invaluable mechanistic and prognostic information. At present, the availability of such data is extremely limited. This article describes the potential utility of a combination of biomarkers in assessing drug-induced alopecia and the protective potential of existing or new treatments. A greater understanding of the precise mechanisms of anti-CIA therapies through biomarker analysis would enhance the rationale, use, and development of such treatments.